Risk Ranking of Open-End Investment Funds in the Republic of Croatia - Ivana Srdarevic; Ivan Kristek (Economic Review: Journal of Economics and Business, 2017)
Risk is an unavoidable situation. Both individuals and business entities are exposed to various types of risk on a daily basis. Since business conducts in contemporary market conditions are characterized by an increasingly higher level of insecurity, business entities have acknowledged the value of risk management. Risk management is a process that entails risk analysis and planning. Risk analysis is a central part of the mentioned process that consists of identification, risk measurement, and assessment of options. Business entities must identify all financial risks that their business conduct is exposed to and quantify them in order to control them. During risk quantification, it is possible to use several methods such as probability analysis, value at risk, and measures of statistical dispersion. After having measured the risk, it is necessary to create a strategy that will efficiently lower exposure to risks and the amount of their influence on business conducts. Investment funds represent a specific possibility of investing financial resources. These are separate assets controlled by investment fund management companies and investors participate in income return of the overall portfolio fund by purchasing shares in investment funds. These funds invest in various financial instruments such as stocks, bonds, and financial resources, and the risk of investment funds depends primarily on the type of financial instruments in which the fund invests. During the purchase of shares in an investment fund it should be taken into consideration that a possible higher income return brings forth a higher level of risk, as in all other types of investments. The aim of this paper is to quantify risk investment funds that conduct businesses in the Republic of Croatia. For this purpose, the measures of statistical dispersion and value at risk will be used.
Keywords: D81; 330; Open-end investment fundsn; risk analysis; Measuring risk